Quercetin postconditioning attenuates myocardial ischemia/reperfusion injury in rats through the PI3K/Akt pathway - Wang,Y. (2013)
Quercetin (Que), a plant-derived flavonoid, has multiple benefical actions on the cardiovascular system. The current study investigated whether Que postconditioning has any protective effects on myocardial ischemia/reperfusion (I/R) injury in vivo and its potential cardioprotective mechanisms. Male Sprague-Dawley rats were randomly allocated to 5 groups (20 animals/group): sham, I/R, Que postconditioning, Que+LY294002 [a phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathway inhibitor], and LY294002+I/R. I/R was produced by 30-min coronary occlusion followed by 2-h reperfusion. At the end of reperfusion, myocardial infarct size and biochemical changes were compared. Apoptosis was evaluated by both TUNEL staining and measurement of activated caspase-3 immunoreactivity. The phosphorylation of Akt and protein expression of Bcl-2 and Bax were determined by Western blotting. Que postconditioning significantly reduced infarct size and serum levels of creatine kinase and lactate dehydrogenase compared with the I/R group (all P<0.05). Apoptotic cardiomyocytes and caspase-3 immunoreactivity were also suppressed in the Que postconditioning group compared with the I/R group (both P<0.05). Akt phosphorylation and Bcl-2 expression increased after Que postconditioning, but Bax expression decreased. These effects were inhibited by LY294002. The data indicate that Que postconditioning can induce cardioprotection by activating the PI3K/Akt signaling pathway and modulating the expression of Bcl-2 and Bax proteins.